Effect of inclination angle on the pulsation frequency of syngas jet fire. (29th January 2023) - Lin, Ziming; Zhao, Kun; Li, Situo; Qian, Jianan; Wang, Hua; Tang, Zhenhua; Cui, Tong; Wang, Zhirong
Abstract: The pulsation frequency of inclined jet fire was systematically studied in this study. Experiments of syngas jet fire with a nozzle diameter of 15 mm at different fuel flow rates (2.5 L/min∼20 L/min) and inclination angles (0°∼90°) were conducted. The pulsation frequency of inclined jet flame is quantified by applying FFT to the time variations of image correlation coefficient, flame height and flame width, corresponding to the global, vertical and spatial pulsation frequencies, respectively. Experimental results indicate that the vertical pulsation frequency can be derived only for jet flames with significant clip-off. The effect of inclination angle on the pulsation frequency depends on the fuel flow rate. For Q f ≤ 7.5 L / min, the natural frequency is dominant and increases slightly at small inclination angles. For larger fuel flow rates, a transition from subharmonic frequency to natural frequency occurs at a critical inclination angle θ c r i, which is sensitive to fuel flow rate. The pulsation behaviors of inclined jet flame are driven by three different instability modes, R-T instability at small fuel flow rates, and Extended R-T and K-H instabilities at larger fuel flow rates. The increase of global pulsation frequency with an increasing inclination angle for Q f ≥ 10 L / min results from the increased natural frequency at the nozzle exit. By defining a characteristic diameter D ∗, a dimensionless model is developed to predict the global pulsation frequency of inclined jet fires with large fuel flow rates, S t = 0.284 ( 1 / F r ) 0.473 for natural frequency and S t = 0.516 ( 1 / F r ) 0.473 for subharmonic frequency. Graphical abstract: Image 1 Highlights: Syngas jet fires with different inclination angles were studied. Global, vertical and spatial pulsation frequencies were obtained based on the FFT method. The transition from natural frequency to subharmonic frequency occurs at a critical inclination angle ( θ c r i ). A global correlation between S t with 1/ F r was obtained by defining a characteristic diameter D ∗.